THE IMPORTANCE OF YOUTH PROTAGONISM FOR HIGH SCHOOL - José Machado da Silva, Luciano (Revista Gênero e Interdisciplinaridade, 2023)
Scientific studies seek to understand the effects of youth protagonism in the educational environment, as well as analyzing the most relevant issues of this phenomenon, such as the need to make the curriculum more flexible and contextualize teaching with the local reality of young people. In this context, the objective of the present study is to analyze the importance of practices that promote youth protagonism in high school. To achieve this objective, a bibliographical review of theses, dissertations and scientific articles collected on Google Scholar was carried out, using the keywords: youth protagonism and high school, in addition to books that deal with this topic. The research indicates that youth protagonism worked in high school is a tool that transforms the learner into a more critical and reflective autonomous subject in the face of the knowledge disseminated in the classroom and in training itineraries that aim to make the curriculum more flexible.